Mechanistic insights into the self-assembly and the interactions of supramolecular gels with biological systems - Angelerou, Maria G. F. (2019)
Among the diversity of drug delivery systems for controlled release, supramolecular gels have recently attracted significant attention due to their biocompatibility and self-healing properties. Supramolecular gels consist of small organic molecules that self-assemble though non-covalent interactions into fibrillar networks that entrap high volumes of solvent (for hydrogels, water). This reversible nature of the interactions that holds the solid phase together is responsible for the dynamic nature of these materials and their responsiveness to multiple external stimuli. The presence of a third (or more) components in the system, apart from the gelator and the solvent, can bring major changes in the properties of the final gels, especially when large biomolecules are encapsulated such as proteins and nucleic acids. These changes are attributed to the interactions occurring among gelator, solvent and encapsulated molecule and it would be expected that any parameter that can affect these interactions can change the properties of the materials. This brings the focus of this work herein on the gelator/encapsulated component interface and the interactions occurring. We start with mechanistic investigations of the principles that govern the gel formation for a 2’-deoxycytidine-based gelator, describing the nanoarchitecture of the solid phase; a network of entangled fibres consisting of a hydrophobic core that generate hydrophilic cavities around them where the solvent mostly resides. On a higher level of complexity, we move on to studying the interactions on simple interfaces between gel and simple chemical functionalities and the effect that these chemical functionalities have on the properties of the self-assembled structures. The property of hydrophobicity and the presence of aromatic nuclei were found to directly affect the supramolecular structures formed. More specifically, the surface properties Polar Surface Area (PSA) and the logP linearly relate with the formation of fibre bundles (fibre aggregation); higher fibre bundle radii are obtained as PSA increases and log P decreases. Additionally, the presence of an aromatic ring leads to higher fibre bundle diameters. Finally, we encapsulate molecules with different properties (a small hydrophobic dye, 1,1'-Dioctadecyl-3,3,3',3'-Tetramethylindocarbocyanine Perchlorate, and different proteins, insulin, lysozyme, β-lactoglobulin and Bovine Serum Albumin) into the supramolecular gels to identify the fibre/encapsulated molecule interactions as well as mechanistically elucidate the in vivo and in vitro release behaviour of these composite systems. The encapsulated molecules were found to directly interact with the fibres through non-covalent interactions (π-π stacking was identified) rather than get physically entrapped and they were released following the gel’s erosion, maintaining their functionality, as demonstrated for insulin and lysozyme. A range of experimental techniques (and molecular dynamic simulations) are used, demonstrating the complementarity of different types of information that need to be accessed to ultimately gain a complete understanding.